The Glass Figure : Prosopopeia and Mourning in André Kertész’s Polaroids - Camacho, Sandra (Revista 2i: Estudos de Identidade e Intermedialidade, 2022)
In this article, I propose to examine how prosopopoeia might be identified in some of André Kertész’s final photographic works, not only in the recourse of a glass figurine, that stood-in for his late-wife, Elizabeth, but also through the analysis of his choice of medium, the Polaroid: an image that holds a distinct material existence, small enough to share, and captivating in its instant development before one’s eyes. Additionally, I will consider the association of prosopopoeia and death, as a literary figure that gives voice to those that have lost it, but also in the very mourning process for Kertész.